DISKURSUS KEARIFAN LOKAL UNTUK PENGEMBANGAN CITY BRANDING MAGELANG KOTA SEJUTA BUNGA - Galih Putra Pamungkas; Achmad Sultoni (Jurnal Bahasa Rupa, 2020)
This research is a discourse to streamline the development of the city branding concept of Magelang City of One Million Flowers by exploring the potential of local wisdom owned by the City of Magelang. Currently, the City of Magelang has the slogan "Magelang City of a Million Flowers". This idea is based on the history of the colonial era which at that time was the City of Magelang better known as Tuin Van Java (Garden City / Park of Java). However, on the one hand, the application of the concept has not yet run optimally. The contributing factor is the incompatibility of the concept with the fact that there is potential and the formation of an image that is not running optimally. According to the potential and the facts of the existing situation, the City of Magelang has great potential by developing the concept as a Heritage City (a city of cultural heritage) which is then followed by the concept of sustainable communication strategies that lead to heritage matters and of course according to aesthetic rules. The Magelang City Government has another choice, which is to continue the Magelang City One Million Flower program, but with the support of visual concepts that utilize all parts of the city to create a communication process by providing direct experience to consumers, namely by utilizing artifacts in the City of Magelang. Artifacts that are part of the culture of the community and have been imprinted in the memory of the community are enhanced with original flower decorations, especially the types of flowers typical of the City of Magelang and its surroundings.